2021
DOI: 10.1002/eap.2308
|View full text |Cite
|
Sign up to set email alerts
|

How does prescribed fire shape bird and plant communities in a temperate dry forest ecosystem?

Abstract: To mitigate the impact of severe wildfire on human society and the environment, prescribed fire is widely used in forest ecosystems to reduce fuel loads and limit fire spread. To avoid detrimental effects on conservation values, it is imperative to understand how prescribed fire affects taxa having a range of different adaptations to disturbance. Such studies will have greatest benefit if they extend beyond short-term impacts of burning. We used a field study to examine the effects of prescribed fire on birds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Data are available from the Dryad Digital Depository: (Rainsford et al. 2021; DOI https://doi.org/10.5061/dryad.qfttdz0gj).…”
Section: Peer Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Data are available from the Dryad Digital Depository: (Rainsford et al. 2021; DOI https://doi.org/10.5061/dryad.qfttdz0gj).…”
Section: Peer Reviewmentioning
confidence: 99%
“…In south‐eastern Australia, for example, post‐fire age classes, determined by compositional and structural changes to vegetation, have been defined to represent key “growth stages” in post‐fire succession in an ecosystem (e.g., Cheal, 2010). Even though much of the fauna of temperate south‐east Australia has not shown strong preferences for particular successional stages (e.g., Rainsford et al., 2021; Swan et al., 2015), the assumption that such categories represent distinct successional communities has rarely been tested for animal taxa.…”
Section: Introductionmentioning
confidence: 99%
“…This can be due to reduced opportunities for dispersal and colonisation (McAlpin, 2001;Lazzari, 2019) and loss of vegetation cover which is ideal for survival of this species (Ridley et al, 2020;Ridley and Schlesinger, 2023). On the other hand, properly prescribed burning can be a driver of species richness and community composition on natural ecosystems (Cadenhead et al, 2016;Rainsford et al, 2021;Zylinski and Swan, 2022). Our study demonstrated that time since the last fire had an influence on dietary diversity though it was not statistically significant (Figure 3).…”
Section: Discussionmentioning
confidence: 69%